PERAMALAN JUMLAH TAMU HOTEL DI KABUPATEN DEMAK MENGGUNAKAN METODE SUPPORT VECTOR REGRESSION - Desy Trishardiyanti Adiningtyas; Diah Safitri; Moch. Abdul Mukid (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
The purpose of this research is to forecast the number of hotel’s guests in Demak using Support Vector Regression. Support Vector Regression (SVR) is method used for forecasting. Forecasting the number of hotel’s guests in Demak using SVR produce good accuracy for forecasting the training and testing data. Forecasting for the training data generate MAPE value of 10.2806% and forecasting of testing data generate MAPE value of 11.622%.Keywords: Support Vector Regression, hotel, Demak, accuracy, forecasting, training, testing